One new species of the genus Acosmetura (Tettigoniidae: Meconematinae) from Hubei, China - Wang, Ping; Bian, Xun; Shi, Fu Ming (Zootaxa, 2016)
One new species of the genus Acosmetura (Tettigoniidae: Meconematinae) is described, namely Acosmetura trigentis Wang, Bian & Shi sp. nov. from Hubei, China. In addition, morphological photographs and a distribution map are provided. The examined specimens are deposited in the Museum of Hebei University.